PRILIKE U ŠKOLSTVU BOSNE I HERCEGOVINE ZA VRIJEME PRIVREMENOG DRŽAVNOG UREĐENJA U KRALJEVSTVU SRBA, HRVATA I SLOVENACA // OPPORTUNITIES IN THE SCHOOL OF BOSNIA AND HERZEGOVINA FOR THE TIME OF THE TEMPORARY STATE ORGANIZATION IN THE KINGDOM OF SRBA, CROATIA AND SLOVENIA - Sead Selimović (Historijski pogledi, 2018)
The school system represents for each country and society one of the most important segments. Because of this, but also a number of other reasons the authorities try to put schools under their control. Through the education of Bosnia and Herzegovina, political, economic, cultural, national and other goals of the ruling political elites were realized. Curricula and curricula eliminated content whose educational goals were in line with the interests of the Austro-Hungarian regime. The ruling elite spread the idea of a "one-tribe nation", striving to create a unique political, economic, educational and cultural space. Teachers who had to respond to the "spirit of time", and curricula and curriculum, had an important place in achieving goals. Significant changes have been made in the group of national subjects (history, geography, Serbian or Croatian language), with emphasis on the history and geography of Serbs, Croats and Slovenians, and works for Serbian school, literature in literature, literature and literature from the Serbian, Croatian or Slovenian literature. The largest number of workbooks were written by authors from Croatia and Serbia, while only a small number were from Bosnia and Herzegovina.